SOCIOECONOMIC OUTCOMES OF CENTRAL GOVERNMENT WELFARE PROGRAMMES: A BENEFICIARY PERSPECTIVE - S. SEETHA LAKSHMI ,Dr. S.UMA MAGESWARI (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Central Government Welfare Programmes play a crucial role in improving the socio-economic well-beingof beneficiaries by enhancing income, education, healthcare, employment, and social security. However, the extent of socioeconomic outcomes varies depending on programme implementation and beneficiarycharacteristics. This study examines the factors influencing the socioeconomic outcomes